Cambridge School Dictionary - Walter, Elisabeth; Woodford, Kate (Cambridge Cambridge University press, 2008)
The perfect companion for learners studying other subjects through english, this dictionnary includes vocabulary from all the main international topics. Clear, simple definitions and grammar and usage information help you on your way to becoming user of english.
Contents.
Keywords: Dictionary; English - English